Nucleation modalities in poly(lactide), poly(butylene succinate), and poly(ε‐caprolactone) ternary blends with partial wetting morphology. Issue 6 (17th August 2020) - Fenni, Seif Eddine; Wang, Jun; Haddaoui, Nacerddine; Favis, Basil D.; Müller, Alejandro J.; Cavallo, Dario
Abstract: Ternary biodegradable polymer blends of poly(lactic acid) (PLA), poly(butylene succinate) (PBS), and poly(ε‐caprolactone) (PCL) with the composition 45/10/45 wt% and exhibiting partial‐wetting morphology were prepared. In this morphology, the minor phase is present as self‐assembled droplets at the co‐continuous interface of the other two major phases. The crystallization of the components in the various blends was thoroughly investigated. Differential scanning calorimetry highlighted minor differences in the overall kinetics of a given component in the ternary blend, with respect to the neat polymer. On the other hand, several unusual nucleation mechanisms could be studied by polarized optical microscopy (PLOM). With reference to the major phases, PLA spherulites displayed surface‐induced nucleation from the interface with molten PBS or PCL droplets. On lowering the crystallization temperature, the PBS phase effectively nucleated at the interface with previously crystallized PLA domains, forming a transcrystalline morphology. Concerning the minor phase, weak partial‐wetting PBS droplets displayed a droplet‐to‐droplet percolation of the nucleation events. Strongly partial‐wetting PCL droplets were confined between previously crystallized PLA and PBS co‐continuous phases and, instead, solidified as isolated domains randomly in space. This work provides further insights in the relationship between morphology and crystallization in immiscible ternary blends. Abstract : Ternary biodegradable polymer blends of poly(lactic acid) (PLA), poly(butylene succinate) (PBS), and poly(ε‐caprolactone) (PCL) with the composition 45/10/45 wt% exhibits partial‐wetting morphology and displayed several nucleation modalities. PLA phase shows surface‐induced nucleation from the interface with molten PBS or PCL droplets. Weak partial‐wetting PBS droplets undergo a droplet‐to‐droplet percolation of the nucleation events, while strongly partial‐wetting PCL droplets were confined between previously crystallized PLA and PBS co‐continuous phases and solidified as isolated domains.